The Effect of Information Quality of the Instagram Account @bemhimaperpusinfo on the Fulfillment of Information Needs of its Followers - Permata, Alvin Tessar; Ummatin, Kuntum Khaira; Rullyana, Gema; Oktaviani, Fikri Dwi (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: Recent studies on social media use in academic settings underline its increasing importance in fulfilling students' information needs.  Still, few studies concentrate on student-run Instagram profiles and how well they meet these requirements.Objective: Particularly in the context of 4C Chris Heuer and Guha's four approaches, this paper sought to examine how the information material given by the Instagram account @bemhimaperpusinfo fulfills the information demands of its followers.Methods: Using a survey design, a quantitative method was applied.  Using many linear models via SPSS 27, data was gathered from 100 followers of the @bemhimaperpusinfo account and evaluated.  Tests of validity, reliability, normality, multicollinearity, and heteroskedasticity were run before the regression analysis to guarantee data quality.Results: According to the study, all four aspects of the 4C Social Media model Context, Communication, Collaboration, and Connection had a notable beneficial impact on followers' information demand fulfillment.  With Communication (β = .380) and Connection (β = .295) rising as the best predictors, the regression model accounted for 72.0% of the variation (R²= .720).  Every 4C variable showed notable correlations with various facets of Guha's information requirements Current, Every day, Exhaustive, and Catching-up.Conclusion: These findings suggest that material created and disseminated by student-led Instagram accounts can significantly help to meet academic and organizational information needs.  Different institutional and peer-managed settings should be investigated in further studies using longitudinal or mixed-method designs to more thoroughly investigate long-term impacts and user experiences.